A General Iterative Algorithm with Strongly Positive Operators for Strict Pseudo-Contractions. (27th March 2013) - Xu, Wei; Wang, Yuanheng
Abstract : This paper deals with a new iterative algorithm { x n } with a strongly positive operator A for a k -strict pseudo-contraction T and a non-self-Lipschitzian mapping S in Hilbert spaces. Under certain appropriate conditions, the sequence { x n } converges strongly to a fixed point of T, which solves some variational inequality. The results here improve and extend some recent related results.